Tenang Dalam Perspektif Hadis - Suherni Suherni; Fadholy Hakim; Nurlaila Nurlaila; Repa Hudan Lisalam (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Calm in the Perspective of hadith refers to the concepts of self-control, inner calm, and patience which are taught and commanded in Islamic teachings. In this study, it was found that calm in the perspective of hadith provides strong guidelines for Muslims in dealing with various life situations. Concepts such as self-control, equanimity, and patience are at the heart of calm which are reflected in these hadiths. Through understanding and practicing these messages, Muslims can develop an attitude of calm that has a positive impact on their mental, emotional and spiritual well-being The purpose of this research is to help Muslims understand the concept of serenity in Islam more deeply. The hadiths that talk about serenity can provide guidance for Muslims to achieve serenity in everyday life. Implementing serenity in life Research on serenity from a hadith perspective can assist Muslims in applying the principles of serenity in their daily lives.